INOVASI SEKTOR PUBLIK DALAM LAYANAN TRANSPORTASI PUBLIK DI KOTA TANGERANG (Studi Kasus Pada Layanan transportasi Umum “Si Benteng”) - Puspitasari, Anggi; Sujana, Nanan; Muhtadi, Yudi (Jurnal Ilmiah Wahana Pendidikan, 2024)
Problems in public transportation "Si Benteng" prompted the Tangerang City Transportation Service to launch the "Si Benteng" public transportation innovation based on problems at PT Tangerang National Global. Postpositivism research paradigm, qualitative research approach and descriptive research with data collection techniques through conducting in-depth interviews with selected informants with high credibility, field observations, and researcher documentation during the research in an effort to obtain relevant information and a high degree of accuracy. The purpose of this research is to find out that PT Tangerang Nasional Global provides behavioral training to drivers, the development of strategies and solutions that must be developed so that people do not have negative perceptions of the "Si Benteng" public transportation program in Tangerang City.